Backstroke start performance: the impact of using the Omega OBL2 backstroke ledge - Barkwell, G. E.; Dickey, J. P. (Sports Biomechanics, 2018)
FINA recently approved the backstroke ledge (Omega OBL2) to improve backstroke start performance in competition, but its performance has not been thoroughly evaluated. The purpose of this study was to compare the mechanics of starts performed with and without the OBL2. Ten high-level backstroke swimmers performed three starts with, and three starts without, the OBL2. A wall-mounted force plate measured the lower limb horizontal impulse, vertical impulse, take-off velocity and take-off angle. Entry distance, time to 10 m and start of hip and knee extension were recorded using video cameras. Starts performed with the OBL2 had a 0.13 s lower time to 10 m, 2.5% less variability in time to 10 m and 0.14 m greater head entry distance. The OBL2 provides a performance advantage by allowing an increased head entry distance rather than larger horizontal impulse on the wall. This may be due to the swimmers assuming different body positions during the start manoeuvre. Additional studies are needed to evaluate factors that contribute to improved performance when using the OBL2. Swimmers should train with the OBL2 and use it in competition to ensure optimal start performance.